Удмурт-ӟуч, ӟуч-удмурт кыллюкам: ог 6500 пала кыл / [редакторы-составители Т. В. Воронова, Т. А. Пояркова] - Воронова Т. В. (Удмуртия, 2015)
Экземпляры: 4 (2016) / Инвентарный номер: 48915 / Цена: 129.00 / Сис.шифр: 81.2(Удм) / Авт.знак: У 30 / ББК: 81.2(2рус.удм)